2019
DOI: 10.1057/s41284-019-00165-x
|View full text |Cite
|
Sign up to set email alerts
|

The dispersion of crime concentration during a period of crime increase

Abstract: Extensive empirical evidence shows that crime concentrates in place, with these findings being important for helping to target police resources. Little is known, however, about whether these crime concentration areas are where crime increases the most during a period of crime increase. Using data from the seven largest cities in the state of Rio de Janeiro, Brazil, we show that during a period of crime increase the locations most responsible for the increases were the micro-places where crime previously concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Our results also support previous research (Chainey and Monteiro 2019) that indicates that differences in population, the volume of crime and crime rates do not appear to be related to differences in crime concentration in Latin American settings. Chainey and Monteiro (2019) suggest that crime concentration is more likely to be related to differences in the distribution of favorable conditions, determined by a combination of specific situational, offending site selection, and neighborhood conditions being present at very few places. Determining the extent of the contribution of each of these factors, and the differences between them in a variety of settings (e.g., comparing Latin American cities to cities in the United States) is a topic worthy of further research on why crime concentration levels vary.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Our results also support previous research (Chainey and Monteiro 2019) that indicates that differences in population, the volume of crime and crime rates do not appear to be related to differences in crime concentration in Latin American settings. Chainey and Monteiro (2019) suggest that crime concentration is more likely to be related to differences in the distribution of favorable conditions, determined by a combination of specific situational, offending site selection, and neighborhood conditions being present at very few places. Determining the extent of the contribution of each of these factors, and the differences between them in a variety of settings (e.g., comparing Latin American cities to cities in the United States) is a topic worthy of further research on why crime concentration levels vary.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…To date, the examination of crime concentration at micro-places has mainly been confined to a number of US-based studies (e.g., Lee et al's, 2017 systematic review of the crime concentration literature did not include any studies from Latin America). However, there is growing evidence that shows these crime concentration patterns are also observed in Latin American urban contexts (Chainey et al, 2019;Jaitman and Ajzenman, 2016;Mejia et al, 2015;de Melo et al, 2015;Pereira et al, 2016;identifying reference). For example, Chainey and Monteiro (2019) found that across five cities in Brazil, 25 percent of all robberies were concentrated in less 2 A street segment is the part of a street between two street junctions.…”
Section: Uruguaymentioning
confidence: 98%
“…Additionally, cameras that see more incidences in their 100m vicinity are ranked higher than those that see less and are thus preferred. The Law of Crime Concentration states that for microgeographic units (such as addresses, facilities, street segments, or small clusters of street segments), crime concentrates within a narrow bandwidth [65,66]. A city can have many of these micro places, often referred to as "hot spots" of crime [67].…”
Section: Proposed Approachmentioning
confidence: 99%
“…A city can have many of these micro places, often referred to as "hot spots" of crime [67]. Studies in Criminology seem to agree that crime concentration is stable over time and that hot spots are not likely to disappear in short periods of time if there is no intervention ( [66,67], and references therein). So, detecting these regions that prevail over time, might help pinpoint locations suitable for action that may have positive benefits in the short and long terms [67].…”
Section: Proposed Approachmentioning
confidence: 99%